2019
DOI: 10.1063/1.5128529
|View full text |Cite
|
Sign up to set email alerts
|

Extension of high power deuterium operation of negative ion based neutral beam injector in the large helical device

Abstract: Second deuterium operation of the negative ion based neutral beam injector (N-NBI) was performed in 2018 in the Large Helical Device (LHD). The electron and the ion current ratio improves to I e /I acc(D) = 0.31 using the short extraction gap distance of 7 mm between the plasma grid (PG) and the extraction grid (EG). The strength of the magnetic field by the electron deflection magnet (EDM) installed in the EG increases 17% at the PG ingress surface, which effectively reduces electron component in the negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Alternative methods to reduce electrons need to be found. For the purpose of reducing the electron flux, three methods were proposed; they are (1) reduction of the plasma flux by expanding the distance between the centre plane of the filter magnets and the plane of PG facing to the source plasma, (2) enhancing the strength of the magnetic field, which is induced with the EDMs, penetrating into the source plasma near the PG apertures by shortening the PG-EG gap from 8 mm to 7 mm [14] and (3) installation of a device named the 'electron fence (EF)' to reduce electron density at the extraction region.…”
Section: − Acceleration and Co-extracted Electronsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative methods to reduce electrons need to be found. For the purpose of reducing the electron flux, three methods were proposed; they are (1) reduction of the plasma flux by expanding the distance between the centre plane of the filter magnets and the plane of PG facing to the source plasma, (2) enhancing the strength of the magnetic field, which is induced with the EDMs, penetrating into the source plasma near the PG apertures by shortening the PG-EG gap from 8 mm to 7 mm [14] and (3) installation of a device named the 'electron fence (EF)' to reduce electron density at the extraction region.…”
Section: − Acceleration and Co-extracted Electronsmentioning
confidence: 99%
“…It is observed that current ratio of electrons to deuterium negative ions (D − ions) extracted from ion source becomes larger than that in the extraction of hydrogen negative ions (H − ions) in the same magnetic configuration and strength. These problems induced with co-extracted electrons decrease injection stability and limit the injection power [6][7][8][9][10][11][12][13][14]. For those reasons above, reduction of co-extracted electrons is one of the main issues in the beam acceleration of n-NBI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, most negative ion source test facilities for fusion operate in hydrogen and only little experience is available on operation in deuterium [5,6]. In order to close this gap in knowledge and experience, the current experimental program at ELISE is focussed on developing advanced operational scenarios for long pulse operation in deuterium.…”
Section: Introductionmentioning
confidence: 99%
“…On LHD, two negative ion injectors with arc sources were firstly operated in 1998 and the third injector was on service in 2001, and each injector has two negative hydrogen ion sources with the design parameters of 180 kV/80 A/5 MW. The totally actual beam power of 7 MW was achieved with the extraction parameters of 180 kV/55.4 A/1.6 s for 3 negative deuterium ion injectors [9]. However, the NBI system with the RF ion source has only been used to ASDEX upgrade tokamak [10].…”
Section: Introductionmentioning
confidence: 99%